2022
DOI: 10.1101/2022.12.28.522121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exact distribution of the quantal content in synaptic transmission

Abstract: The transfer of electro-chemical signals from the pre-synaptic to the post-synaptic terminal of a neuronal or neuro-muscular synapse is the basic building block of neuronal communication. When triggered by an action potential the pre-synaptic terminal releases neurotransmitters in the synaptic cleft through vesicle fusion. The number of vesicles that fuse, i.e., the burst size, is stochastic, and widely assumed to be binomially distributed. However, the burst size depends on the number of release-ready vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…We start by reviewing the SHS formalism for capturing the timing of AP-generation in the postsynaptic neuron [27], [29], [30]. Later in this section, we extend the model to implement negative feedback via an autapse.…”
Section: Formulating Neurotransmission As a Stochastic Hybrid Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…We start by reviewing the SHS formalism for capturing the timing of AP-generation in the postsynaptic neuron [27], [29], [30]. Later in this section, we extend the model to implement negative feedback via an autapse.…”
Section: Formulating Neurotransmission As a Stochastic Hybrid Systemmentioning
confidence: 99%
“…Given that there are M − n ( t ) empty sites, the net replenishment rate is k ( M − n ( t )). This stochastic replenishment process can be probabilistically defined as Combining (3) with (1), the two resets driving the stochastic dynamics of n ( t ) can be represented together as Using the standard tools of moment dynamics [32], we had previously shown that the first and second-order statistical moments of the scalar integer-valued random process n ( t ) evolve as where the angular brackets ⟨ ⟩ denote the expected-value operation [27], [29]. Solving these equations at steady state yield Our prior work has investigated the steady-state noise levels in both n , and the number of released vesicles b , as a function of model parameters f, M, k, p r [27], [30], and also shown the utility of these results in the inference of parameters from experimental data [28].…”
Section: Formulating Neurotransmission As a Stochastic Hybrid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…3). This is in contrast to the case of deterministic arrivals (i.e., time between successive APs are fixed), and in this case Fano factors ≤ 1 are subPoissonian across parameter regimes [28], [40].…”
Section: Quantifying Statistics Of Neurotransmissionmentioning
confidence: 99%
“…no resets back to resting potential). Clearly, for (28) to be defined v s > v th which leads to result that if…”
Section: Connecting Neurotransmitter Activity To Postsynaptic Ap Firingmentioning
confidence: 99%